The only road - Diaz, Alexandra (Simon & Schuster Books for Young Readers, 2017)
When Jaime hears his cousin Miguel murdered outside his house in Guatemala, Jaime knows he either needs to get out or get hurt next. With his cousin °ngela, Jaime leaves for the United States, risking everything for a chance at a new, safe life.